Regulation of EZH2 by SMYD2-Mediated Lysine Methylation Is Implicated in Tumorigenesis - Yi Zeng; Rongfang Qiu; Yang Yang; Tianyang Gao; Yu Zheng; Wei Huang; Jie Gao; Kai Zhang; Ruiqiong Liu; Shuang Wang; Yongqiang Hou; Wenqian Yu; et al. (Cell Reports, 2019)
Summary: The histone methyl transferase enhancer of zeste homolog 2 (EZH2) is a master transcriptional regulator involved in histone H3 lysine 27 trimethylation. We aimed to elucidate the precise post-translational regulations of EZH2 and their role in cancer pathogenesis. Here, we show that SET and MYND domain containing 2 (SMYD2) directly methylates EZH2 at lysine 307 (K307) and enhances its stability, which can be relieved by the histone H3K4 demethylase lysine-specific demethylase 1 (LSD1). SMYD2 is critical for EZH2 function in repressing a cohort of genes governing several cancer-associated pathways. In addition, SMYD2 promotes breast cancer cell proliferation, epithelial-mesenchymal transition, and invasion through EZH2 K307 methylation, and it is markedly upregulated in various human cancers. Our data suggest that dynamic crosstalk between SMYD2-mediated EZH2 methylation plays an important role in fine-tuning EZH2 functions in chromatin recruitment and transcriptional repression. : Post-translational modification of proteins is involved in protein stability regulation. Zeng et al. demonstrate that EZH2 K307 is methylated by SMYD2 and demethylated by LSD1. This modification protects EZH2 from degradation. The dynamic crosstalk between SMYD2-mediated EZH2 methylation plays an important role in the transcriptional repression of EZH2. Keywords: methylation, tumorigenesis, breast cancer, EZH2, SMYD2, post-translational modification